2019
DOI: 10.1038/s41598-019-39837-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RNAi-based silencing of chitin synthase gene on moulting and fecundity in pea aphids (Acyrthosiphon pisum)

Abstract: The pea aphid, Acyrthosiphon pisum , is an important agricultural pest and an ideal model organism for various studies. Chitin synthase (CHS) catalyses chitin synthesis, a critical structural component of insect exoskeletons. Here, we identified a CHS gene from A . pisum , ApisCHS . The ApisCHS expression profiles showed that ApisCHS was expressed in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 48 publications
(60 reference statements)
5
43
0
4
Order By: Relevance
“…We believe the expressions of 25 core genes upon the dsRNA treatment are dose-dependent as well as in sufficient dose presenting a time points-based dynamics. For instance, the response of core machinery was detected in both 24 h [36] and 36 h in the current study. In addition, the RNAi efficiency of the targeted gene was the highest at the 36 h [36].…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…We believe the expressions of 25 core genes upon the dsRNA treatment are dose-dependent as well as in sufficient dose presenting a time points-based dynamics. For instance, the response of core machinery was detected in both 24 h [36] and 36 h in the current study. In addition, the RNAi efficiency of the targeted gene was the highest at the 36 h [36].…”
Section: Discussionsupporting
confidence: 48%
“…This trend occurred in the dsGFP treated sample but not in the dsHB treated sample. We previously observed that the induction of these three genes occurred 24 h after dsRNA injection (600 ng per aphid) [36], implying that the variation of gene expression level induction is associated with the time of sample collection and the physiological stage of the aphids. We believe the expressions of 25 core genes upon the dsRNA treatment are dose-dependent as well as in sufficient dose presenting a time points-based dynamics.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This method was also used in the brown citrus aphid, Aphis citricidus , for silencing genes encoding insulin receptors, vitellogenin, 3‐ketoacyl‐CoA thiolase, and glycogen phosphorylase . In Acyrthosiphon pisum , silencing of the chitin synthase 1 gene through leaf‐based dsRNA delivery disrupted nymph molting and embryo development …”
Section: Introductionmentioning
confidence: 99%
“…2,12,13 In Acyrthosiphon pisum, silencing of the chitin synthase 1 gene through leaf-based dsRNA delivery disrupted nymph molting and embryo development. 14 Insect cuticle is the primary protective barrier against environmental stresses. 15,16 The main structural components of the cuticle are chitin, lipids, catecholamines, minerals, and cuticle proteins (CPs).…”
Section: Introductionmentioning
confidence: 99%